Adaptation of Muhadharah Model as a Strategy to Improve Speaking Skills in Elementary Schools - Zumrotus Sa'diyah; Zaenal Abidin (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
Abstract: This study examines how religious activities can be utilised as a means of developing speaking skills and as a platform for practising speaking in Indonesian language lessons at primary level. The problems discussed in this study are the limited opportunities for students to practice speaking and the low self-confidence shown during oral activities in class. Using a qualitative descriptive approach, this study was conducted at Sumberkerep Public Elementary School by implementing Muhadharah as a routine religious activity for fourth-grade students. Data were collected through classroom observations, field notes, and semi-structured interviews with students and teachers. The results of the study indicate that religious activities such as Muhadharah, which involve role rotation as host, prayer leader, speaker, and poetry and rhyming verse reciter, provide structured and meaningful opportunities for students to practice speaking in public. Students showed increased confidence, improved fluency, and a greater willingness to speak in front of their peers in a supportive religious environment. In conclusion, this study shows that religious activities can be effectively integrated as a pedagogical strategy to train speaking skills while strengthening students' religious and character development.